2010
DOI: 10.1007/s13238-010-0082-2
|View full text |Cite
|
Sign up to set email alerts
|

A loop matters for FTO substrate selection

Abstract: Recent studies have unequivocally established the link between FTO and obesity. FTO was biochemically shown to belong to the AlkB-like family DNA/RNA demethylase. However, FTO differs from other AlkB members in that it has unique substrate specificity and contains an extended C-terminus with unknown functions. Insight into the substrate selection mechanism and a functional clue to the C-terminus of FTO were gained from recent structural and biochemical studies. These data would be valuable to design FTO-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Han et al . (22) presented the structural and biochemical work providing insight into the substrate selection mechanisms of FTO , and Rendo et al . (23) reviewed the role of FTO on adiposity based on lifestyle intervention studies in children and adolescents.…”
Section: Research On Fto – Strategies For Novel Obesity‐associated Locimentioning
confidence: 99%
“…Han et al . (22) presented the structural and biochemical work providing insight into the substrate selection mechanisms of FTO , and Rendo et al . (23) reviewed the role of FTO on adiposity based on lifestyle intervention studies in children and adolescents.…”
Section: Research On Fto – Strategies For Novel Obesity‐associated Locimentioning
confidence: 99%
“…FTO encodes a nuclear protein that is orthologous to proteins of the AlkB family of deoxygenases and appears to function as a DNA or RNA demethylase (Han et al, 2010). In mice and rats, manipulations of Fto gene expression have produced changes in body weight, but not in a consistent direction (Stratigopoulos et al, 2008, 2011; Wang et al, 2011; Tung et al, 2010; Church et al, 2010), and humans heterozygous for null alleles of FTO show no consistent effects on body weight (Meyre et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, a mere buffer solution cannot recapitulate the tremendous compositional complexity of the cellular environment. Furthermore, changes of molecular environment from one subcellular compartment to another could easily alter the enzyme’s behaviour 44 . In cellulo studies on FTO offer a striking illustration of this.…”
Section: Towards Tissue-specific Function?mentioning
confidence: 99%
“…The C-terminal domain of FTO does not contain essential residues for RNA interaction or FTO activity. Noteworthy, comparative studies have shown that FTO’s C-terminal domain is unique compared to the other ALKBH family members [ 44 , 51 . The versatile activity of FTO is likely due to this domain, through its ability to associate with molecular partners.…”
Section: Determinants Of Multi-substrate Specificity Of Ftomentioning
confidence: 99%